Foucault's monsters and the challenge of law - Sharpe, Andrew N. (Taylor and Francis, 2009)
This book considers the legal category 'monster' from theoretical and historical perspectives and deploys this category in order to understand contemporary anxieties surrounding transsexuals, conjoined twins and transgenic humans.